Peer-Delivery of a Gender-Specific Smoking Cessation Intervention for Women Living in Disadvantaged Communities in Ireland We Can Quit2 (WCQ2)—A Pilot Cluster Randomized Controlled Trial. Issue 4 (20th November 2021) - Hayes, Catherine B; Patterson, Jenny; Castello, Stefania; Burke, Emma; O'Connell, Nicola; Darker, Catherine D; Bauld, Linda; Vance, Joanne; Ciblis, Aurelia; Dobbie, Fiona; Loudon, Kirsty; Devane, Declan; et al.
Abstract: Introduction: We Can Quit" (WCQ) is community-based stop-smoking program delivered by trained community facilitators, based on the socio-ecological framework and developed using a Community-based Participatory Research approach, targeting women living in socioeconomically disadvantaged (SED) areas of Ireland. Aims and Methods: The We Can Quit2 (WCQ2) pilot trial assessed the feasibility of WCQ. A pragmatic cluster randomized controlled trial with a process evaluation WCQ2, was conducted in four matched pairs of SED districts (8–10 000 women per district). Districts were independently randomized to WCQ (group support + nicotine replacement therapy), or to individual support delivered by health professionals. Participants were adult women smokers interested in quitting, who were living or working in trial districts. Recruitment of districts and 194 women in four waves (49 women per wave); retention at 12 weeks and 6 months; fidelity to intervention delivery and acceptability of trial-related processes were assessed. Validated smoking abstinence at 12-week and 6-month post-intervention was recorded, missing data assumed as continued smoking. Results: Eight districts were recruited. 125/188 (66.5%) eligible women consented. The 49 women target was reached in wave4. Retention at 12 weeks was (Intervention [I]: 55.4%; Control [C]: 51.7%), at 6 months (I: 47.7%; C: 46.7%). Smoking abstinence at 12 weeks was (I: 23.1%, [95% CI: 14.5 to 34.7]; C: 13%, [95% CI: 6.9 to 24.1]). 83.8% of session activities were delivered. Trial-related processes were acceptable to facilitators. Low literacy was highlighted as a barrier for participants' acceptability. Conclusions: WCQ was feasible to deliver by trained facilitators and indicated a positive direction in abstinence rates. Low literacy will need to be addressed in a future trial design. Implications: This pilot trial showed that a stop-smoking intervention tailored to a group of women smokers living in SED areas which was delivered by trained local women within their local communities was feasible. Furthermore, although not formally compared, more WCQ women were abstinent from smoking at the end of treatment. The results are relevant to enhance the design of a fully powered effectiveness trial, and provide important evidence on the barriers to deliver a tailored smoking cessation service to SED women smokers in Ireland.